Effect of a Smoking and Substance Abuse Prevention Program by Using Islamic Principles on Health Literacy on Smoking and Substance Abuse Prevention among Muslim Youth in Private Religious Schools in Three Southern Border Provinces - Ranee, Sarinah; Langputeh, Prapaporn; ์Nimu, Nisuraida (Journal of Behavioral Science for Development, 2022)
The objective of this research is to compare the average scores of health literacy in smoking and drug prevention among Muslim youth in the three southern border provinces before and after participating in using Islamic principles. The program was developed by integrating Islamic principles into the concept of health literacy promotion based on the V-Shape model which consists of 6 elements: access, understanding, response and questioning, decision-making, behavioral adjustment and communicable. The sample consisted of 100 male Muslim junior high school students selected by purposive sampling. Research instruments consisted of the health literacy on smoking and substance abuse prevention assessment. Reliability of questionnaire was tested using Cronbach’s alpha coefficient, yielding a value of 0.87. Data were analyzed using dependent t-test. The study found that overall mean scores of the health literacy on smoking and substance abuse prevention of the majorities after participated in the program (M=80.49, SD = 1.54) were increased than before (M=107.40, SD =1.10) and statistically significant (P<0.05) Suggestions for policy implications are Smoking and Substance Abuse Prevention Program by Using Islamic Principles helps to promote health literacy on smoking and substance abuse prevention among Muslim youth. The program should be applied as a further protection tool against new smokers among Muslim youth in other schools both private and public to increase smoking and substance protection skills among the youth effectively and lead to measurement of preventing the increase of new smokers and substance abuse among youth.